Biometrics in The Quran Perspective: Definition, History, and Type - Huda, Syamsul; Yusuf, Enjang Burhanudin (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2019)
The Qur’an is the holy book which is inexhaustibly studied by many people. It has inspired a lot of thoughts, research and studies. The discussions of human in the Qur’an are numerous, ranging from the creation, life, naming, relationships of one another, and etc.. The Qur’an mentions that man is created in the perfect form, which is given advantages over other creatures. With his intellectual power, human tries to explore knowledge about him and understand his nature as a creature of God. Biometrics views human as a unique being. Biometrics sees that parts of the human body can be used as a security device because each human has his special uniqueness different from one another. Because of this specificity, human invents devices that refer to all materials, types of equipment, labours, and man-made systems to replicate the existing systems in nature. At present, the scientific community really needs such a device, especially in the field of nanotechnology, robot technology, artificial intelligence, medicine and military. Biometric normally used in the form of authentification, including Introduction to Fingerprint, Face Recognition, Recognition Retina or Iris, Geometry Arm, Geometry Finger, introduction of Palms, Voice Recognition, Introduction to Signatures, DNA (Deoxyribonucleic Acid), Thermal Imaging (Body Temperature), Shape Ear, Body Odor, Body Movement. On some types of biometric authentication on top of the al-Qur’an gives a signal on Surah Fussilat [41]: 20-22.